Prevalence of Parvovirus B19 Specific Antibody in Pregnant Women with Spontaneous Abortion - Nahid Rahbar; Saeid Vali Zadeh; Raheb Ghorbani; Pegah Kheradmand (Acta Medica Iranica, 2015)
Human parvovirus B19 is a very common viral infection especially in school-aged children. The infection during pregnancy can affect the fetus due to lack of mother's immunity. Although, there is still no evidence of fetal teratogenic effects with parvovirus B19, but non-immune fetal hydrops and abortion may be caused by vertical transmission of the virus during pregnancy. This study was aimed to assess the prevalence of parvovirus B19-specific antibody (IgM) in pregnant women who had a spontaneous abortion. This cross-sectional study was carried out in all pregnant women who referred due to a spontaneous abortion. All demographic information such as age, occupation, and gestational age, last history of abortion, gravity, and presence of children below the age of six was recorded and a blood sample was provided for all the women. Then, the blood samples were tested to assay parvovirus B19-specific antibody (IgM) by EuroImmune ELISA kit. Among 94 pregnant women with the mean age of 28.4 years who had a spontaneous abortion, parvovirus B19 specific antibody (IgM) was detected in 17 participants (18.1%). Meanwhile, 14 women (14.9%) were suspected for presence of the antibody in their blood sample. There was no significant difference between the presence of antibody and age of pregnant women, occupation, gestational age, number of previous abortion, presence of children below the age of six and number of pregnancy. These findings revealed that a high percentage of pregnant women are probably non-immune against parvovirus B19, and also there might be a number of spontaneous abortions in which parvovirus infection caused fetal death.  However, more studies are needed to prove the absolute role of parvovirus B19 in these abortions.